Nomenclatural and taxonomic notes on Rubus sect. Corylifolii (Rosaceae) in Central Europe - Király, Gergely (Phytotaxa, 2019)
During recent herbarium and field studies three names of Rubus sect. Corylifolii ser. Subcanescentes were re-assessed. Rubus macrostemonides was typified with a neotype specimen from Salzburg (Austria), and its identity with R. baruthicus was shown (the previous name has the priority). Its presence at the Austrian locus classicus was confirmed also recently, this locality represents the easternmost occurrence of the species. The name R. holosericeus was (mis)applied for a long time for a widespread taxon occurring southeast of the Alps that is not at all present in the original material. This name was lectotypified with a specimen from Styria (Austria) here as a hitherto overlooked regional species recently recorded in Austria, Hungary and Slovenia. The taxon that was formerly (mis)identified as R. holosericeus has proven to be identical to R. semitomentosus, which is lectotypified here with a specimen from Hungary. For both taxa clarified here is, beside a circumstantial assessment of the type material, an improved morphological characterization and circumscription of distribution and habitats presented.